ISLAM DAN KONSTITUSI: ANALISIS-KOMPARATIFANTARA TEKS AL-QURAN DENGAN PASAL 29 UUD 1945 - Rahman Mantu (IAIN Manado, 2018)
The Constitution as the legal basis is a general agreement of the citizens regarding basic norms and basic rules in the state, which became known as the 1945 Constitution. As a general agreement, the 1945 Constitution is an attempt to find common ground and reconciliation of various values and interests of citizens, including the values and norms of Religion, in this case Islam. This paper will provide reference naqliyyah arguments for the provisions contained in the 1945 Constitution. The authors focus on taking part one that is article 29 of the 1945 Constitution. To find where the intersection between al Quran texts with the sounds of article 29 the author uses a comparative analysis of the text. The result between the constitution with the source of Islamic teachings that the Quran, have the same spirit substantially, fight for humanity and uphold justiceKonstitusi sebagai dasar hukum merupakan kesepakatan umum warga negara mengenai norma dasar dan aturan dasar dalam bernegara, yang kemudian dikenal dengan Undang-undang Dasar 1945. Sebagai, kesepakatan umum, UUD 1945 merupakan usaha pencarian titik temu dan rekonsiliasi dari aneka nilai dan kepentingan warga negara, termasuk di dalamnya nilai dan norma Agama, dalam hal ini Islam. Tulisan ini akan memberikan rujukan dalil-dalil naqliyyah untuk ketentuan yang dimuat dalam UUD 1945. Penulis fokus mengambil satu bagian yaitu pasal 29 UUD 1945.Untuk mencari dimana titik temu antara teks al Quran dengan bunyi pasal 29 penulis menggunakan pendekatan analisis komparatif atas teks. Hasilnya antara konstitusi dengan sumber ajaran Islam yakni al Quran, punya semangat yang sama secara substansial, memperjuangkan kemanusian dan menegakkan keadilan.